The Antioxidant Effect from the Milky Juice Of Lepidium Meyenii Walpers (Maca) In Experimental Animals With Caused Osteoporosis - Benavides R., Elena R. (2008)
We evaluate the maca antioxidant effect in albino rats to observe its influence in the development of osteoporosis. Twenty five (25) four month female albino rats were used and divided ¡nto five groups. Gl a control group and four sample groups (G2, G3, G4 and G5) were forced to have osteoporosis with heparina 2U / gl every other day for a thrce week period, at the same time they were given antioxidants (G3) and natural products (maca, G4 and soya, GS) where G2 the osteoporosis c( ntrol group. At the end of thi5 period blood and urine samples were taken for the analysis of catalase(CAT) and dismutase super oxide (SOD) to evaluate the antioxidant effect and Hidroxiprolina urine and calcium as indicators in the lose out of calcium (resorbtion osea). The G2 which presented osteoporosis showed an increase in their antioxidants enzymes while maca was the natural product which presented reasonable results in comparison with the one obtained in group G3 which were given vitamin CE and selenite and the group GS which were given soya. Therefore we could observe the favorable maca consumption against the osteoporosis evolution. In conclusion maca could be used as an alternative and in the prevention and treatment of this illness.